The Influence of Organizational Justice on Managers’ Decision-Making: A Critical Literature Review - Hussein, Khalil Anwar (European Scientific Journal, ESJ, 2024)
This paper focuses on studying organizational justice on managers’ decision making. The process of decision making plays a substantial role in the life of each organization because the results affect all employees at all levels. Making decisions is considered the most significant and intricate managerial task. In addition, it might become more problematic when executives work with people across cultures since individuals from varied cultural backgrounds view issues differently. Decisions that are formed by senior managers are mostly imperative and impactful to the way an organization works. However, senior managers’ decisions may have negative effects. In addition, organizational fairness is complex and refers to the fair and right treatment of persons within an organization. As a result, people would like fairness as it recompenses them for their input. Poor organizational justice is a considerable reason for negative responses from staff because they have a strong sense of inequality. Often, ethical dilemmas result from intricate circumstances and discrepancies in values within organizations. Hence, this theoretical paper is designed to investigate the salient literature to develop a holistic overview portraying the individual level of perceived organizational justice. It also indicates its prominent consequences based on a critical review of previous related studies.